1991
DOI: 10.1128/jvi.65.9.4670-4680.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DNA polymerase gene of human herpesvirus 6

Abstract: The construction of a recombinant bacteriophage A library containing overlapping clones covering 155 kbp of the 161-kbp genome of the Ugandan U1102 isolate of human herpesvirus 6 (HHV-6) is described. The use of degenerate-primer polymerase chain reaction allowed the isolation of a DNA probe for the DNA polymerase gene of HHV-6, which was subsequently used to isolate and position the pol gene on the physical map of the viral genome. A 4.4-kbp EcoRI DNA restriction fragment containing the pol gene was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 59 publications
0
26
0
1
Order By: Relevance
“…The mutation in D1/3/4 and D6/3/1 is found between regions IV and A. The homology among herpesvirus DNA polymerases sequences remains high between these two regions, although the sequence conservation is not found outside this virus group (12,34).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The mutation in D1/3/4 and D6/3/1 is found between regions IV and A. The homology among herpesvirus DNA polymerases sequences remains high between these two regions, although the sequence conservation is not found outside this virus group (12,34).…”
Section: Resultsmentioning
confidence: 94%
“…4). The leucine residue at position 501 which is changed to isoleucine in both D6/3/1 and D1/3/4 is conserved in all human herpesvirus DNA polymerases (34). The phenylalanine residue at position 412 which is changed to valine in D10/3/2 is con-POLYMERASE MUTANTS OF HUMAN CYTOMEGALOVIRUS Standards consisting of GCV and GCV monophosphate were run on the same column to determine relative retention times.…”
Section: Resultsmentioning
confidence: 99%
“…Domain II is one of the most conserved regions of the herpes virus DNA polymerases [Larder et al, 1987;Teo et al, 1991] and has been suggested as a strong candidate for the pyrophosphate binding site [Larder et al, 1987]. On the basis of genetic analysis of HSV and HCMV resistant strains [Larder et al, 1987;Gibbs et al, 1988;Baldanti et al, 1996], it was observed that amino acid substitutions which confer PFA-and/or PAA-resistance are clustered in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Two PFA-resistance [Gibbs et al, 1988;Wong et al, 1988;Hwang et al, 1992]. Below is shown the amino acid sequence of domains II and III from a number of herpesvirus DNA polymerase including : HSV-1, HSV-2, EBV, CMV, HHV-6 [Teo et al, 1991], and HHV-7 [Nicholas, 1996]. Amino acids identical to the VZV sequence are shaded and on consensus (CON), point indicates amino acid relatively conserved in all herpes viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This assay consists of multiplex PCR amplification to detect simultaneously HSV-1, HSV-2, VZV, EBV, CMV, HHV-6A and HHV-6B genomes that are expected to be present in a single specimen, and DNA microarray hybridization to identify accurately the specific PCR products. DNA polymerase gene of human herpes viruses has been reported as a highly conserved and homogeneous gene [Teo et al, 1991] and it was selected as the target gene in this study. Primers and oligonucleotide probes were designed on the conserved regions of this gene.…”
Section: Discussionmentioning
confidence: 99%